Using the SWAT model to assess impacts of land use changes on runoff generation in headwaters. Issue 3 (17th December 2012) - Wang, Guoqiang; Yang, Huicai; Wang, Lijing; Xu, Zongxue; Xue, Baolin
Abstract The upstream regions of the Three Gorges Reservoir (TGR) have undergone significant changes in land use during recent years, and these changes have strongly influenced runoff generation downstream. In this study, the relationships between land use changes and corresponding hydrological responses in the Dong and Puli River basins in the upstream region of the TGR were quantified using the runoff coefficient. Empirical regression equations between the runoff coefficient and the percentage of land use types were developed for the study area using partial least squares regression (PLSR). The Soil and Water Assessment Tool was used to simulate the runoff generation processes in the two basins, and land use maps developed using Landsat Thematic Mapper images from 2000, 2005, and 2010 were compared to extract information on changes in land use. The results showed that the total area of forest and pasture decreased over the 10‐year study period, while paddy fields and upland increased in both basins. These land use changes dramatically affected hydrological processes. Evapotranspiration decreased by 2.13% and 2.41% between 2000 and 2010 in the Dong and Puli River basins, respectively, whereas quickflow, infiltration, and baseflow increased to varying degrees. The PLSR modeling results showed that upland had a negative effect on the runoff coefficient and was the most influential land use type in the study area. In contrast, a positive effect of forest on runoff generation was found in most of the regression models. Copyright © 2012 John Wiley & Sons, Ltd.